Dark pool trading strategies, market quality and welfare - Buti, Sabrina; Rindi, Barbara; Werner, Ingrid M. (Journal of Financial Economics, 2017)
We show that when a continuous dark pool is added to a limit order book that opens illiquid, book and consolidated fill rates and volume increase, but spread widens, depth declines, and welfare deteriorates. The adverse effects on market quality and welfare are mitigated when book-liquidity builds but so are the positive effects on trading activity. All effects are stronger when traders’ valuations are less dispersed, access to the dark pool is greater, horizon is longer, and relative tick size larger.